Chemistry and light - Suppan, P.; Pasquier-Bird, Ann M. ([S.l.] : Royal Society of Chemistry, 1994)
This text provides a concise introduction to all aspects of light-induced processes in chemistry, physics and biology, as well as in medicine and industry. It is up to date with the latest advances in the field, in particular the probing of the fastest light-induced reactions on picosecond and femtosecond time scales, and is based on the photochemistry and photophysics degree course devised by the author. Chemistry and Light is a must for final year undergraduates, as well as for post-graduate students. It will prove extremely useful for teachers in the preparation of courses and seminars and will provide essential background information for industrial chemists, in one complete source. The book reflects the enthusiasm the author has for his subject, as well as his talent for clear description. Chemistry and Light will be welcomed by students and research workers alike.
Keywords: chemitry,light